Biomass Processing Network Optimisation Using P-graph with Pareto Screening - Wendy P. Q. Ng; Elida A. R. Ngu; Nur Faakhirah binti Haji Ahmadbi; Hon Loong Lam (Chemical Engineering Transactions)
A global movement is working towards emission reduction. Despite its availability, biomass is generally under-utilised due to various challenges, including financial factors. Convincing economic and environmental performances of biomass waste-to-wealth processing networks are needed to motivate investors and boost the implementation of biomass projects. In this work, the P-graph is combined with Pareto visualisation to optimise and screen biomass waste-to-wealth processing network to generate optimal models for investors’ selection. The selected optimal solution generates an annual gross profit of MYR 210 M and a total carbon emission of 69 kt CO2. This work aims to motivate the development of the biomass industry by providing a convincing statement to the palm industry and investors for investment and development.